Subnational Targeting of Project Sites Using Project Targeting Index - Finn, Arden; Masaki, Takaaki (World Bank, Washington, DC, 2020)
It is critical to ensure that the World Bank portfolio is well targeted to areas with the greatest needs and with greatest potential to maximize development benefits. The Project Targeting Index (PTI) offers an evidence-based approach to inform spatial targeting of projects based on country strategies and objectives. We apply the PTI method for case studies in Madagascar and South Sudan to demonstrate how the tool helps align and monitor Bank project locations with development goals.